Creating mutual benefits: examples of gender and biodiversity outcomes from Bioversity International’s research - Gender and Social Inclusion Community of Practice (Bioversity International, 2017)
Bioversity International uses a gender lens to support the differentiated gender-specific knowledge and priorities linked to women’s and men’s access and management of resources. Women and men have different aspirations, skills and knowledge. The following pages comprise a series of fact sheets featuring Bioversity International case studies with local NGOs and partners. These case studies illustrate successful outcomes in gender and biodiversity through the use of gender-specific research methods.